The Effect of Distribution Costs and Distribution Channels on the Sales of PT. Pasha Jaya Medan - Muhammad Hafiandi Prahada; Muhammad Yamin Siregar; Sugito Sugito (Universitas Medan Area, 2022)
Distribution basically is the activity of delivering products from the hands of producers to the hands of consumers or customers in good condition, on time and in accordance with the wishes of the buyer. The distribution process can be done either directly or through a chain of distributors or intermediaries. In distribution activities, there must be distribution costs and distribution channels. Distribution costs and distribution channels must be managed properly in order to have a positive impact on sales. The purpose of this study was to determine the effect of distribution costs and distribution channels on sales of PT. Pasha Jaya Medan. The population in this study amounted to 9 companies that bought PT. Pasha Jaya Medan. Each of these companies, taken 5 respondents so that the total sample amounted to 45 respondents. Samples were taken using a saturated sampling technique. (significant effect on the sales of PT. Pasha Jaya Medan, Distribution Channel ( no significant effect on the sales of PT. Pasha Jaya Medan, and Distribution Costs and Distribution Fees simultaneously affect the sales of PT. Pasha Jaya Medan.